Toward understanding sexual immune dimorphism in humans - Tomasz J. Nowak; Michael P. Muehlenbein (Frontiers in Immunology)
Sexual immune dimorphism refers to the distinct differences in immune responses between males and females, influenced by genetic, hormonal, developmental, social, and behavioral factors. These differences, shaped by evolutionary pressures, manifest in varied susceptibilities to infectious and autoimmune diseases, as well as differences in vaccine responses and disease outcomes. Females generally exhibit stronger immune responses than males, which confer protection against infections but also lead to a higher prevalence of autoimmune diseases. Hormones such as estrogen, progesterone, and testosterone play pivotal roles in modulating these responses. Estrogen enhances immune activation, promoting inflammation and increasing autoimmune susceptibility, while testosterone exerts primarily immunosuppressive effects, reducing autoimmune risks but heightening infection susceptibility. Genetic factors, including X-linked immune-related genes and cellular mosaicism, further contribute to the observed dimorphism, as do epigenetic mechanisms that modulate immune gene expression. From an evolutionary perspective, life history theory explains these differences as the result of trade-offs between reproductive strategies and immune function, with females prioritizing robust immunity for offspring survival and males balancing immune investment with reproductive fitness. Behavioral factors, such as pathogen avoidance and risk-taking, add complexity to the dimorphism. This review adopts a narrative format intentionally designed to provide a cohesive conceptual synthesis of major mechanisms underlying sexual immune dimorphism. While acknowledging the complexity and breadth of this topic, we explicitly focus on integrating hormonal, genetic/epigenetic, behavioral, and evolutionary contexts. By examining the interplay of these factors, the review provides a foundation for understanding the biological underpinnings and evolutionary context of immune differences between sexes.